2022
DOI: 10.1039/d2ta02598a
|View full text |Cite
|
Sign up to set email alerts
|

Halide sublattice dynamics drive Li-ion transport in antiperovskites

Abstract: Proton incorporation and halide mixing allow for lower synthesis temperatures and more rapid processing of cubic lithium antiperovskites. Halide mixing softens halide-sublattice dynamics for improved Li+ transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 54 publications
7
18
0
Order By: Relevance
“…, which have a span of ±500 ppm for Li 2 OHCl at room temperature, 6 not observable in our Li 2 OHCl sample at room temperature before the transition to cubic from orthorhombic, in conjunction with the facilitated Li + ion mobility. In addition, we confirmed that the observed line widths of the peaks are primarily due to the homonuclear dipole−dipole interactions (i.e., 7 Li− 7 Li), rather than heteronuclear dipolar interactions (such as 7 Li− 1 H), on the basis of the 7 Li NMR spectral line width obtained at 353 K, with and without 1 H decoupling (see Figure S3) and the separation of the rotational correlation times between Li + ions and OH − groups. 7 Consequently, the line widths of the 7 Li NMR spectra in these samples are strongly correlated with the mobility of Li + ions.…”
Section: ■ Results and Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…, which have a span of ±500 ppm for Li 2 OHCl at room temperature, 6 not observable in our Li 2 OHCl sample at room temperature before the transition to cubic from orthorhombic, in conjunction with the facilitated Li + ion mobility. In addition, we confirmed that the observed line widths of the peaks are primarily due to the homonuclear dipole−dipole interactions (i.e., 7 Li− 7 Li), rather than heteronuclear dipolar interactions (such as 7 Li− 1 H), on the basis of the 7 Li NMR spectral line width obtained at 353 K, with and without 1 H decoupling (see Figure S3) and the separation of the rotational correlation times between Li + ions and OH − groups. 7 Consequently, the line widths of the 7 Li NMR spectra in these samples are strongly correlated with the mobility of Li + ions.…”
Section: ■ Results and Discussionsupporting
confidence: 73%
“…The static 7 Li NMR spectra of the series of samples are shown in Figure 1. The peak at ∼0 ppm corresponds to the central transition (m…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations